Gliomatosis cerebri in children: a poor prognostic phenotype of diffuse gliomas with a distinct molecular profile - Nussbaumer, Gunther; Blattner-Johnson, Mirjam; Pfister, Stefan; Sturm, Dominik; Jones, David T. W. (Neuro-Oncology, 2024)
The term gliomatosis cerebri (GC), a radiology-defined highly infiltrating diffuse glioma, has been abandoned since molecular GC-associated features could not be established.We conducted a multinational retrospective study of 104 children and adolescents with GC providing comprehensive clinical and (epi-)genetic characterization.Median overall survival (OS) was 15.5 months (interquartile range, 10.9-27.7) with a 2-year survival rate of 28%. Histopathological grading correlated significantly with median OS: CNS WHO grade II: 47.8 months (25.2-55.7); grade III: 15.9 months (11.4-26.3); grade IV: 10.4 months (8.8-14.4). By DNA methylation profiling (n = 49), most tumors were classified as pediatric-type diffuse high-grade glioma (pedHGG), H3-/IDH-wild-type (n = 31/49, 63.3%) with enriched subclasses pedHGG_RTK2 (n = 19), pedHGG_A/B (n = 6), and pedHGG_MYCN (n = 5), but only one pedHGG_RTK1 case. Within the pedHGG, H3-/IDH-wild-type subgroup, recurrent alterations in EGFR (n = 10) and BCOR (n = 9) were identified. Additionally, we observed structural aberrations in chromosome 6 in 16/49 tumors (32.7%) across tumor types. In the pedHGG, H3-/IDH-wild-type subgroup TP53 alterations had a significant negative effect on OS.Contrary to previous studies, our representative pediatric GC study provides evidence that GC has a strong predilection to arise on the background of specific molecular features (especially pedHGG_RTK2, pedHGG_A/B, EGFR and BCOR mutations, chromosome 6 rearrangements).